Stock Market Development, Bank Concentration, Ownership Structure, and Bank Performance: Evidence from Turkey - Hasan Ayaydin; İbrahim Karaaslan (Journal of Economics and Political Economy, 2014)
Using the the Two-Step Generalized Method of Moments (GMM) described by Arellano and Bond (1991) for dynamic panels, this paper analyzes the profitability of 25 commercial banks in Turkey over the period from 2003 to 2011.Our profitability determinants include bank-specific characteristics as well as industry-specific and macroeconomic factors, some of which have not been considered in previous studies. We conclude that the high bank profitability during these years is associated with a large percentage of loans in total assets, a low proportion of liquid asset, good efficiency and a low doubtful assets ratio. In addition, higher capital ratios also increase the bank's return, but only when return on assets and return on equities is used as the profitability measure. We find evidence of economies of scale in the Turkish banking sector. Empirical results show that there is a negative relationship between financial development and profitability. We find also there is a positive relationship between bank concentration and bank performance in Turkish banking industry, consisting with the structure-conduct-performance (SCP) hypothesis. The results also suggest that there is a negative relation between the foreign ownership and profitability, indicating that foreign banks do not in general make relatively higher profit, at least during the period under the consideration.
Keywords: G21; C32; E44; 330; Banking profitability; Stock markets; Concentration; Ownership; Turkey; GMM